(untitled) (Altre Modernità, 2017)
Eoin Devereux, Aileen Dillane and Martin J. Power (eds.), David Bowie: Critical Perspectives (New York and London, Routledge, 2015, 323 pp. ISBN 978-0-415-74572-7) by Pietro Deandrea